Sejarah Peradaban Islam di Turki - Fahmi Jalaluddin; Nurkhalishah; Syamsudhuha Saleh; Bahaking Rama (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to examine the history of Islamic civilization in Turkey by analyzing the development of the Ottoman Empire and its transformation into the modern era. The research employs a qualitative method using a historical approach and library research. Data were collected from relevant scholarly literature and academic journals discussing Islamic history in Turkey, particularly in political, educational, and cultural aspects. Data analysis was conducted using a descriptive-analytical technique by interpreting historical events based on their periodization. The findings reveal that the Ottoman Empire played a central role in establishing a powerful and globally influential Islamic civilization. The integration of Islamic values into governance, legal systems, and educational institutions was a key factor in the advancement of Islamic civilization in Turkey. Despite the decline of the Ottoman Empire and the implementation of secularization policies during the Republican era, Islamic values have continued to persist within Turkey’s social and cultural life. This study concludes that Islamic civilization in Turkey demonstrates a dynamic and adaptive character in responding to historical changes.AbstrakPenelitian ini bertujuan untuk mengkaji sejarah peradaban Islam di Turki dengan menelaah perkembangan Dinasti Turki Usmani hingga transformasi menuju era modern. Penelitian ini menggunakan metode kualitatif dengan pendekatan sejarah dan studi kepustakaan. Sumber data diperoleh dari berbagai literatur dan jurnal ilmiah yang relevan dengan sejarah Islam di Turki, khususnya yang membahas aspek politik, pendidikan, dan kebudayaan. Teknik analisis data dilakukan secara deskriptif-analitis dengan mengkaji peristiwa sejarah berdasarkan periodisasi perkembangan peradaban. Hasil penelitian menunjukkan bahwa Dinasti Turki Usmani memainkan peran sentral dalam membangun peradaban Islam yang maju dan berpengaruh secara global. Integrasi antara nilai-nilai Islam dan sistem pemerintahan, hukum, serta pendidikan menjadi faktor utama kejayaan peradaban Islam di Turki. Meskipun mengalami kemunduran dan sekularisasi pada era Republik Turki, nilai-nilai Islam tetap bertahan dalam kehidupan sosial dan budaya masyarakat. Penelitian ini menegaskan bahwa peradaban Islam di Turki bersifat dinamis dan adaptif terhadap perubahan zaman.